Sex education in adolescence: Can the nurse help? - Martins, Ivani Pose; Santos, Jeniffer Stefany de Souza; Silva, Liliane Aparecida da Costa; Vieira, Lívia Maria; Leal, José Carlos; Mota, Sandra de Almada; Barbosa, Fernando Sérgio (Seven Editora, 2024)
The study aims to analyze how much adolescents have been oriented regarding sexuality. Articles and studies published in recent years (2018-2022) in the Portuguese language, which addressed sex education in adolescents, were searched in the literature. Throughout the study, adolescents aged 13 to 19 years, students from all over the Brazilian federation, in schools and health centers, in public educational institutions, female and male, were approached, based on the work of nurses for guidance. With the role of the nurse in the education of adolescents for guidance on preventive methods, prevention against unwanted pregnancies and on safe relationships, they will be able to learn what they do not receive at school or at home, they will be able to be open to questions with the health professional, who is more oriented to answer these doubts and solve the problems faced by these generations. DOI:https://doi.org/10.56238/sevened2024.007-060